Averral at Yakoot al- Hamwi and the role of the author - زرده , يوسف; ديّوب , هيفاء; مرعي السليمان العبدالله, عبدالرحمن (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research is held to discuss the art of averral at the Yakoot al- Hamwi, and to explain the role of the author in it: Is it merely a carrier of the averral, or is it formulated up to oral accounts or written personal formulation, in order to show the importance of the historical, social, and intellectual in the Arab civilization; In enriching the material of many Arab blogs, and in enhancing its knowledge value, which made it the ether art form that absorbed all the poetry, Converses, Causeries, Councils and debates that enabled it to take a prominent place in the Arab heritage, as well as to deny saying the role of the Arab Author after the Hijri centuries The first Ih only on transport. Therefore, the research presents a definition of the averral language and terminology and then the meaning of the averral in the narrative, and then deals with the role of the author in the averrals contained in the authors of the (Dictionary of writers), and (Dictionary of countries) applied study, talking about the role of Yakoot in the transmission of averral by talking about: The author The carrier, the critical author, the creative author, and finally the research ends with reading his findings.